Angelina Branković – święta władczyni w hymnografii. Zarys problemu - Gapska, Dominika (Wydawnictwo Naukowe UAM, 2013)
The aim of this article is to present the idea of divinity of power on an example of the medieval service, dedicated to the Serbian despotess Angelina Branković. The image of a ruler and a concept of power presented in the text are based on the perception of Angelina as a participant and a heiress of the sacred tradition of Branković dynasty. The service has played an important role in the creation and strengthening of the ruler image in the spiritual culture of the Orthodox Serbs. In addition to strictly liturgical function, it also served as a way of transmission of the elementary set of national religious and political ideas. Hymnography dedicated to St. Angelina was a response to the social and religious needs to canonize the native saints who certify God’s care for Serbiain the period of slavery, strengthen the national spirit, contribute to stabilizing the situation in the country.
Angelina Branković: the Holy Ruler in Hymnography. Outline of the Problem
Keywords: Serbian Orthodox Church; the Serbian hymnography; St. Angelina Branković; divinity of power; Serbian female saints; topos of a ruler